Given that
"(8x-x^2y)dy+(x-xy^2)dx=0"
There is no specified method mentioned in the question. So, I used exact method to solve this.
Taking "x-xy" as common
"(x-xy)((8-x)dy+(1-y)dx)=0"
"(8-x)dy+(1-y)dx=0"
"(1-y)dx+(8-x)dy=0"
The above equation is in the form of
"M(x,y)dx+N(x,y)dy=0"
"M(x,y)=(1-y)" and "N(x,y)=(8-x)"
"\\frac{\\partial M}{\\partial y}=-1" and "\\frac{\\partial N}{\\partial x}=-1"
"\\frac{\\partial M}{\\partial y}=\\frac{\\partial N}{\\partial x}"
So, the equation is exact.
So, the general solution is
"\\int Mdx+\\int (" terms of N not involving x)"dy=c" (here c is the constant)
"\\int (1-y)dx +\\int 8dy=c"
"x-xy+8y=c"
So, the solution is "x-xy+8y=c"
Comments
Leave a comment